Health knowledge of lifestyle-related risks during pregnancy: a cross-sectional study of pregnant women in Germany - Oechsle, Anja Maria; Wensing, Michel; Ullrich, Charlotte; Bombana, Manuela (International journal of environmental research and public health, 2020)
This study aimed to investigate (1) pregnant women’s level of knowledge of lifestyle-related risk factors during pregnancy and their potential health impact on their offspring, and (2) the factors affecting women’s knowledge of lifestyle-related risk factors during pregnancy. A cross-sectional observational study of pregnant women was carried out in obstetric and gynecologic care settings at three hospitals in Southern Germany. Data from 209 pregnant women revealed large knowledge gaps on lifestyle-related risk factors during pregnancy and their potential health impact. Factors affecting women’s knowledge of lifestyle-related risk factors during pregnancy were specifically associated with socioeconomic status, e.g., lower household net income, middle educational level, and statutory health insurance status. Women who had received information from their gynecologist had a higher level of knowledge of lifestyle-related risk factors during pregnancy. This study showed that health promotion regarding lifestyle-related risks during pregnancy specifically needs to address women from the low-to-middle socioeconomic status group. Gynecologists seem particularly effective in providing this information.
Gesehen am 13.01.2021